Integration of microfluidic channel on electrochemical-based nanobiosensors for monoplex and multiplex analyses: An overview - Hussaini, Adam; Subash, C.B. Gopinath; M.K, Md Arshad; Tijjani, Adam; Uda, Hashim; Zaliman, Sauli; Fakhri, Makram A.; Sreeramanan, Subramaniam; Chen, Yeng; Sreenivasan, Sasidharan; Wu, Yuan Seng * (Elsevier, 2023)
Background Microfluidic devices have evolved into low-cost, simple, and powerful analytical tool platforms. Herein, an electrochemically-based microfluidic nanobiosensor array for monoplex and multiplex detection of physiologically relevant analytes is reviewed. Unlike other analyte detection methods, microfluidics-based embedded electrochemical nanobiosensors are portable, custom electrochemical readers for signal reading.